Kahoot Game-Based Learning Design in Teaching English for Vocational School Using Genre-Based Approach Model - Izzah, Amniyatul; Sujana, I Made Sujana; Saputra, Agus; Melani, Boniesta Zulandha; Munanda, La Ode Alfin Haris (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
Vocational high schools aim to prepare students with the skills necessary to enter the world of work directly, including mastery of the English language. However, challenges remain, such as teachers' limited understanding of innovative teaching methods and a lack of interactive and contextual learning resources tailored to students' professional needs. This Research is a collaborative research type of Research and Development (R&D) that aims to design English teaching modules using Kahoot game-based learning for vocational schools, utilizing ESP (English for Specific Purposes) and the Genre-based Approach model. This research procedure is the ADDIE model. The module design follows the GBA stages: Building Knowledge of the Field (BKOF), Modeling of the Text (MOT), Joint Construction of Text (JCOT), and Independent Construction of Text (ICOT), with Kahoot integrated to foster student involvement and participation. Expert validation resulted in high scores for media (98.33%) and material (93.84%), which shows the feasibility of the module. Application to 33 hospitality students at SMKN 4 Mataram showed increased enthusiasm and active learning. Student responses rated this module as very effective (89.32%). These findings highlight Kahoot's potential to improve learning outcomes and engagement in English vocational education to meet specific industry needs.